Nanoindentation induced piezoelectricity in SrTiO3 single crystals - Bdikin, I.
Nanoindentation-induced polar properties in (0 0 1)-oriented SrTiO3 single crystals were analysed using piezoresponse force microscopy and local Raman spectroscopy measurements. The area directly beneath the indenter showed a strong piezoelectric response, together with an enhanced response in the area along the direction tangential to the residual indent. Stress-induced stable polarization states near the crack areas were also observed. Local poling performed on the strained areas suggests a possibility of polarization reversal and the stability of field-induced polar states. (C) 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.